A need analysis for development of online advertising e-booklet on entrepreneurship education - Mujiati, Desy Wahyuningrum; Muslim, Suyitno; Febriana, Rina (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This research aims to describe the results of the needs analysis for the development of online marketing e-booklet learning media in entrepreneurship subjects. In this research, the needs analysis refers to: (1) The great opportunity to become an entrepreneur in the Food & Beverage (F&B) Study Program because of the presence of online sales application technologies such as Gofood, Grabfood, and the Open PO sales system; (2) The problem of theoretical learning entrepreneurship; (3) Media needed in online marketing practices. This research uses survey, observation, interview and literature study methods in collecting data. The results of a survey conducted on alumni of SMK Tata Catering, namely 96% stated that attractive product images could attract consumers; 94% agree that making attractive drawings is part of entrepreneurship lessons. The results of the book literature study used marketing material is theoretical. The results of observations on students of class XI Catering and interviewing entrepreneurship teachers at SMK 1 Tambun Selatan found that: 1) Teachers still teach Offline marketing methods; 2) There is no interactive learning media to make online advertising on product marketing in entrepreneurship subjects. The results of this study concluded that students need interactive learning media in learning activities. Thus, this research is used in developing online advertising marketing e-booklet media on entrepreneurial subjects.